PENGARUH KUALITAS SISTEM INFORMASI, PERSEPSI KEMUDAHAN PENGGUNAAN, DAN PERSEPSI MANFAAT TERHADAP KEPUASAN WAJIB PAJAK BADAN PENGGUNA E-FILING DI KPP PRATAMA SURAKARTA - Apriliani, Chintya; Suharno, Suharno; Widarno, Bambang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The imrpovement of taxation services can be seen with the development of modern tax administration and information technology in various aspects of activities. Changes that done bye the modernization of taxes to fulfill the aspirations of taxpayers by simplifying the procedures for reporting tax returns using the e-filing system. e-Filing is a tax reporting/ submission system with SPT electronically conducted through a real time online system. The purpose of this study is to analyze the effect of information system quality, perceived ease of use, and perceived benefits on satisfaction of taxpayers of e-Filing user corporate in the City of Surakarta. With sampling techniques using coenvenience sampling. Analysis techniques used are multiple linear regression, t test, f test, and R2. The results of this study indicate that the quality of the information system, perceived ease of use, and perceived benefits have a significant positive effect on satisfaction of taxpayer of e-filing users corporate in the City of Surakarta.